Lectin-like activity of components extracted from human glomerular basement membrane. - Gerfaux, J (1979)
Different fractions of human glomerular basement membranes have been isolated by enzymatic and chemical methods. These fractions were analyzed for their chemical structure and biological activity. The hypothesis that human glomerular basement membrane glycopeptide fractions related to collagenous sequences could act as a lectin-like substance was explored; in fact, extracellular glycoprotein factors play a role in cell-cell interactions and cell adhesion. These collagenous glycopeptides agglutinate human transformed or embryonic cells within 2 hr. The cell agglutination is inhibited by the following sugars: N-acetylglucosamine, N-acetylgalactosamine, and N-acetylneuraminic acid. In addition, the rapid cytoagglutination is followed by a cell spreading effect after a further 20-hr incubation. These data led to the postulate that the maintenance of tissue differentiation is governed by the interaction of cells with peculiar sites of the basement membrane consisting of a proteolysis-resistant association between collagen and matrix glycoprotein.